An adipo-osteoprogenitor population in the endosteal niche contributes to bone and fat formation in adult mouse bone marrow - Xueyang Liao; Jasmin Koehnken Sawall; Rebecca Seeley; Fangfang Song; Xing Ji; Xiaobin Liu; Chao Song; Fanxin Long (Proceedings of the National Academy of Sciences, 2025)
The adult bone marrow houses progenitors for both osteoblasts and adipocytes, but their precise molecular identity remains to be fully elucidated. Previous studies indicate that Lepr + Cxcl12 + bone marrow stromal cells collectively give rise to both osteoblasts and marrow adipocytes, but the high degree of heterogeneity among those cells calls for further delineation of common or lineage-specific progenitors in vivo. Here, by single-cell RNA-sequencing we identify a small subset of bone marrow stromal cells coexpressing Adipoq and Osx, along with other osteogenic or adipogenic genes. The Adipoq + Osx + cells predominantly reside in the endosteal niche. Intersectional genetic fate mapping with Dre and Cre recombinases demonstrates dual differentiation of osteoblasts and adipocytes from the Adipoq + Osx + cells in vivo. The data support the Adipoq + Osx + cells as adipo-osteoprogenitors contributing to bone and fat formation in the adult mouse bone marrow.